Nutritional Composition and In Vitro Digestibility of Spent Mushroom Substrate Supplemented with Urea and Molasses for Ruminants - Crisostomo, J. C. A.; Manlapig, J. J. D.; Matsui, H.; Ban-Tokuda, T. (Tropical Animal Science Journal, 2025)
This study aims to evaluate the fermentation characteristics and nutritional potential of spent mushroom substrates (SMS), with or without urea and molasses supplementation, in ruminant diets. SMS derived from the cultivation of four mushroom species—Pleurotus ostreatus (Oyster Mushroom, OYS), Flammulina filiformis (Enoki mushroom, ENK), Hypsizygus marmoreus (Bunashimeji mushroom, SMJ), and Lentinula edodes (Shiitake, STK)—were analyzed for proximate composition, in vitro gas and methane (CH₄) production, dry matter digestibility (DMD), and short-chain fatty acid (SCFA). Statistically significant differences were observed among SMS types across all incubation periods (24, 48, and 72 hours) for gas production, CH₄ production, DMD, and SCFA concentrations (p<0.0001). In addition, CH₄ per gram of digested dry matter (CH₄/DDM) was higher in urea–molasses supplemented SMS compared to non-supplemented substrates (p<0.05). However, no significant differences were observed in total gas production, CH₄ volume, or SCFA concentrations between the two groups, suggesting that fermentation responses were influenced not only by supplementation but also by the inherent differences in substrate composition. The results indicate that different types of SMS vary significantly in their fermentation profiles and digestibility. Supplementation with urea and molasses increased CH₄/DDM but did not significantly affect total gas, CH₄ volume, or SCFA production. These findings demonstrate the potential of SMS as a partial roughage replacement in ruminant diets, as influenced by the type of mushroom substrate, its chemical composition, and the supplementation method.